How to End the COVID-19 Pandemic by March 2022 - Agarwal, Ruchir; Reed, Tristan (World Bank, Washington, DC, 2021)
How can the world reach herd immunity against COVID-19 before the second anniversary of the pandemic, or March 2022? A study of vaccine demand and supply answers this question. A target of vaccinating 60 percent of the population in each country by March 2022 is likely sufficient to achieve worldwide herd immunity under a baseline scenario with limited mutation. Achieving this target appears feasible given stated production capacity of vaccine manufacturers and the pace of current and historical vaccination campaigns. Considering existing pre-purchase contracts for vaccines, achieving this target requires addressing a procurement gap of just 350 million vaccine courses in low- and middle-income countries. Immediate additional donor funding of about $4 billion or in-kind donations of excess orders by high-income countries would be sufficient to close this gap. There are additional challenges along the path to achieving world-wide herd immunity---including supply chain issues, trade restrictions, vaccine delivery, and mutations. Overall however, this analysis suggests multilateral action now can bring an end to the acute phase of the pandemic early next year.